ЖАНУБИЙ ОРОЛ БЎЙИ ВА ХОРАЗМНИНГ ҚАДИМГИ ДАВРДАГИ ҚУРОЛСОЗЛИК ҲУНАРМАНДЧИЛИГИ - Турганов, Б.Қ. (SCIENCE and SOCIETY, 2023)
The article, based on written sources and archaeological materials, examines the weapon craft of the Southern Aral Sea region and Khorezm in the ancient period. The region has produced weapons since the Bronze Age. The manufacture of weapons became a specialized industry in the 7th-6th centuries BC. During this period, armor for riders and her horses began to be produced, as well as weapons such as bows, daggers, swords, spears and battle axes.
Keywords: South Aral Sea; khorezm. ancient authors; tribes of Saks and Massagets; military affairs; weapons; bows; daggers; armor and battle axes; Achaemenid army; Greco-Persian wars